Thematic Interpretation Law and Justice of the Ministry of Religion Republic Indonesia: (Analysis of Maqasid al-Shari’ah and ad-Dakhil wal-Ashil) - Sam'ani; Rohman, Taufiqur (Hikmatuna : Journal for Integrative Islamic Studies, 2020)
This article was written with the aim of knowing a comprehensive description of the thematic interpretations of the Ministry of Religion of the Republic of Indonesia concerning law, justice and human rights from the perspective of maqasid al-shari'ah and ad dakhil wal ashil analysis which has not been done much. Even though in the midst of the reality of a pluralistic life such as Indonesia, this is urgent to do. This is proven by the unpopular use of law, justice and human rights from a thematic interpretation perspective by considering maqasid al-shari'ah and ad-dakhil wal-ashil. This study uses a library research model with a qualitative-verification approach. The data collection method uses the documentation method. The analysis results show that thematic interpretation of law and justice at Thematic Tafsir of Ministry of Religion of the Republic Indonesia has taken into account the source of authentic interpretation (al-ashil), comprehensive knowledge related to the principles of the science of interpretation and the conditions that must be met by the team of interpreters, and there is no distorted interpretation because all the interpreters have the mastery.